CHMP4A in hepatocellular carcinoma: exploring its role in tumor progression, immune modulation, and potential link to TIM3 checkpoint - Sun, Kai; Wen, Song; Guo, Shou-jun; Pan, Qing-hua; Wang, Ke-run (Frontiers in Immunology, 2025)
BackgroundCharged Multivesicular Body Protein 4A (CHMP4A), a member of the ESCRT-III family, plays a pivotal role in membrane remodeling and fission, with emerging evidence underscoring its significance in cancer immunotherapy. The complex pathogenesis and therapeutic resistance characteristic of liver hepatocellular carcinoma (LIHC) present significant challenges in clinical practice. This study investigated the potential involvement of CHMP4A in the progression of LIHC.Methods and resultsUtilizing a comprehensive pan-cancer analysis with datasets from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), ArrayExpress database and the International Cancer Genome Consortium (ICGC), we evaluated the prognostic significance of CHMP4A, its clinical implications, associated signaling pathways, DNA methylation status, immune cell infiltration, and response to chemotherapy. Bioinformatics analyses, corroborated by immunohistochemical validation, revealed a marked overexpression of CHMP4A in LIHC specimens relative to adjacent normal tissues. Kaplan-Meier survival analyses indicated that this elevated expression pattern was associated with poor patient outcomes. Single-cell transcriptomic analysis had identified NK/T cells and tumor cells as the predominant cellular sources of CHMP4A within the LIHC microenvironment. Functional studies employing CHMP4A-specific small interfering RNA (siRNA) revealed significant inhibition of malignant phenotypes in LIHC cells, notably affecting proliferation, migration, and invasive capabilities. Mechanistically, the knockdown of CHMP4A led to modulation of the epithelial-mesenchymal transition (EMT), as indicated by the upregulation of E-cadherin and the concurrent downregulation of vimentin and matrix metalloproteinases (MMP-2/9). A comprehensive analysis of the immune landscape demonstrated significant correlations between CHMP4A expression patterns and various immunological parameters, including immune cell infiltration, expression of checkpoint molecules, tumor mutational burden (TMB), and microsatellite instability (MSI). Notably, the silencing of CHMP4A markedly decreased the expression levels of the TIM3/LGALS9 immune checkpoint axis in LIHC.ConclusionsOur extensive analyses identified CHMP4A as a critical molecular determinant in the progression of LIHC, which may function through two oncogenic mechanisms: the promotion of tumor cell proliferation and metastatic potential, and immunomodulatory effects associated with the TIM3/LGALS9 signaling pathway. These findings indicated that CHMP4A might serve as a potential therapeutic target and prognostic biomarker in LIHC.